General Aspects of Recreational Angling and Some Estimations on Catch Amounts in Turkey - Ozan Soykan; Hasan Cerim (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2018)
Some simple approaches make easy to see problems that lie at the centre of the phenomenon. Contrary toexpectations of outputs at the decision given may originate from lack of this simple approaches. From this pointof view, recreational angling performed by hundreds of thousands or millions of people, has serious effects onboth ecosystem and economy. Recreational angling known as a daily activity. Even though its outputs indicatedin a few local, estimation of its effects in every parts of Turkey can be light on legislative regulations. Alloweddaily recreational catch limit is 5 kg per person in Turkey. But coupled with this amount and conjectural anglernumbers, an unseen situation is transpired. It was aimed in this study, besides state of recreational angling inTurkey, comparing of annual catch of recreational angling with Turkey total fishery, inland and marine capturefishery statistics. Also economic gains from this activity and lack of knowledge about legislative regulationsdraw the attention.